Dileucine ingestion, but not leucine, increases lower body strength and performance following resistance training: A double-blind, randomized, placebo-controlled trial. - Anthony M Hagele; Joesi M Krieger; Connor J Gaige; Kevin F Holley; Kristen N Gross; Joshua M Iannotti; Leah E Allen; Paige J Sutton; Logan S Orr; Petey W Mumford; Martin Purpura; Ralf Jager; et al. (PLoS ONE)
Background The essential amino acid leucine (LEU) plays a crucial role in promoting resistance-training adaptations. Dileucine (DILEU), a LEU-LEU dipeptide, increases MPS rates, however its impact on resistance training outcomes remains unexplored. This study assessed the effects of DILEU supplementation on resistance training adaptations. Methods Using a randomized, double-blind, placebo-controlled approach, 34 resistance-trained males (age: 28.3 ± 5.9 years) consumed 2 grams of either DILEU monohydrate (RAMPS™, Ingenious Ingredients, L.P.), LEU, or placebo (PLA) while following a 4-day per week resistance training program for 10 weeks. Changes in body composition, 1-repetition maximum (1RM) and repetitions to failure (RTF) for leg press (LP) and bench press (BP), anaerobic capacity, countermovement jump (CMJ), and maximal voluntary contraction (MVC) were assessed after 0 and 10 weeks. Results Significant main effects for time (p < 0.001) were realized for LP and BP 1RM and RTF. A significant group × time interaction was identified for changes in LP 1RM (p = 0.02) and LP RTF (p = 0.03). Greater increases in LP 1RM were observed in DILEU compared to PLA (p = 0.02; 95% CI: 5.8, 73.2 kg), and greater increases in LP RTF in DILEU compared to LEU (p = 0.04; 95% CI: 0.58, 20.3 reps). No significant differences were found in other measures. Conclusions DILEU supplementation at 2 grams daily enhanced lower body strength and muscular endurance in resistance-trained males more effectively than LEU or PLA. These findings suggest DILEU as a potentially effective supplement for improving adaptations to resistance training. NCT06121869 retrospectively registered.